Niveles de compost y sus efectos en el cultivo de Brassica oleracea L., col repollo, var. capitata, cultivar corazón de buey, en Zungarococha – Loreto 2022 - Rios Diaz, Hugo Sebastian (2023)
The thesis was carried out in order to study the behavior of the levels of compost of stubble of the banana crop, in the cultivation of Brassica oleracea L., cabbage, var. capitata, cultivate Ox heart, in a land of clay loam texture, where it was fertilized with levels of 30, 40, 50 and 60 t / ha with the aim of determining the best level of fertilization in each of the characters and yield of the crop. The land was conditioned to form microplots of 2.5 m2, performing the compost fertilization according to the levels of study raised, reaching the following conclusions: The compost involved in the increase of the average values of the characteristics and yields of the Cabbage, Ox Heart; the level of compost (60 t/ha), presented the best results of the characteristics and yield; with a level of 60 t of compost / ha was presented the yield of 419 g of head weight and 8,380 Kg of head weight / ha; The higher the level of composting, the greater the results; the Level of 60 t of compost / ha obtained the best utility in S / .17,120.00